School. A Recent History of Self-organized Art Education. - Thorne, Sam (Berlin : Sternberg Press, 2017)
Bruguera, Tania ; Vidokle, Anton ; Ögüt, Ahmet ; Vilensky, Dmitry ; Helguera, Pablo ; Dockray, Sean ; Silva, Bisi ; Gander, Ryan ; Jakobsen, Jakob ; Shawky, Wael ; Eliasson, Olafur ; Tohme, Christine ; Haeg, Fritz ; Colin, Anna ; Van der Pol, Bik ; Tounte, Maya ; Taylor, Laurence; Golia, Piero ; Arrubla, Andrea
A chronicle of self-organized art schools and artis run educationplatforms that have emerged since 2000. Conversations conducted with artists, curators and educators. Spanning projects in Londen, Lagos, Los Angeles, Mexico City, Ramallah, Berlin and St Petersburg. The pedagogical turn, student debt, the future of art education. The Silent University, Picasso in Palestine, Manifesta 6, unitednationsplaza, Night School, Hannah Arendt Institute for Artivism, The School of Pan-American Unrest, Open School East, School of Missing Studies, ...
boek